역사문화자원을 활용한 경주시의 도시브랜드 전략 연구 -시각적 표현요소 분석을 중심으로 - 조정정; Cao Ting Ting; 이홍; Lee Hong; 안병진; Ahn Byoung Jin (기초조형학연구, 2023)
본 연구목적은 역사문화자원을 활용한 경주 도시브랜드 전략을 심벌마크, 슬로건, 로고의 시각적 표현요소를 중심으로 분석하여 도시브랜드 전략 과제와 추진방향에 대한 시사점을 제공하는 것이다. 연구방법은 역사문화자원, 도시브랜드 전략, 경주 연구보고서, 학위논문, 학술지 등 문헌을 참고한다, 분석기준은 선행연구를 근거로 심벌마크(표현적 의미, 함축적 의미), 슬로건(언어 표기, 의미 유형), 로고(로고 유형, 로고 기호 유형)로 설정함으로써 경주 도시브랜드 전략 사례 중 시각적 표현요소를 분석한다. 그 결과, 첫째, 경주 심벌마크 표현적 의미는 통일신라의 권위와 문화유산인 황금색 왕관, 신라건국의 기반이 된 육부촌을 의미하는 여섯 개의 흰 점, 첨성대의 문인 회색로 나타나고, 의미는 과거통일신라의 역사와 문화자원을 형상화한 것으로 나타나 있다. 둘째, 경주 슬로건의 언어 표기는도시명을 포함하며, 표기 형식은 영어, 의미 유형은 금색 ‘골든 시티’와 청색 ‘경주’로 표현하여 신라 역사문화와 관광도시로서 경주의 미래와 가능성을 함축하고 있다. 셋째, 경주 로고는 심벌마크와 타이포그래피가 조합된 유형이며, 기호 유형은 과거 신라의 위상을 상징하는 상징형있다. 넷째, 경주의 시각적 표현요소 문제점은 영어 슬로건을 사용해 한국 역사도시이자 통일신라에 기반한 지역성이 부각되지 않으며, 심벌마크에 사용된 기호 표현 요소의 의미를 직관적으로 인지하기 어려워, 통일신라를 제외한 스마트 관광도시를 추구하는 경주만의 도시정체성이 부각되지 않다. 따라서 경주의 도시브랜드 전략과제와 추진방향으로 도시브랜드 아이덴티티 디자인의 재정비, 경주를 특징적 요소 도출, 지역민의 생활방식, 도시문화, 역사문화적 특성을 토대로 한 도시정체성 구축을 주장한다. 본 연구는 글로벌 관광도시를 지향하는 국내 도시들이 일관된 도시정체성을 구축하도록 도시브랜드 전략에서 도시 정체성의 탐색이 체계적으로 선행되어야 한다는 시사점을 제시하한다. The purpose of this study is to analyze Gyeongju city brand strategy using historical and cultural resources, focusing on the visual expression elements of symbol marks, slogans, and logos, to provide inspiration for city brand strategy task and direction. Research methods refer to historical and cultural resources, city brand strategy, Gyeongju research reports, papers, academic journals. Analysis criteria are based on prior research, symbol marks (expressive meaning, implicit meaning), slogans (linguistic notation, semantic type), logos (logo type, logo symbol type)，analyzes the visual expression elements of Gyeongju city brand strategy. As a result, first, the expressive meanings of Gyeongju symbol mark is the golden crown of Unified Silla’s authority and cultural heritage，the six white dots represent the six villages on which Silla was founded, the gray gate of Cheomseongdae, the meaning is to visualize the historical and cultural resources of Unified Silla in the past. Second, the language notation of Gyeongju slogan include the city name, the format is English, semantic types are gold “Golden City” and blue “Gyeongju”, implying the future and potential of Gyeongju as a historical culture and tourist city of Silla. Third, Gyeongju logo is a combination of symbol marks and typography, the symbol type is a symbol of Silla's past status. Fourth, Gyeongju’s visual expression element uses English slogans, it cannot highlight the local characteristics of Korean historical cities and unified Silla. It’s difficult to intuitively recognize the meaning of the symbol expression elements used in the symbol mark, so the unique urban identity of Gyeongju, which pursues a smart tourism city, is not prominent except Unified Silla. Gyeongju city brand strategy mission is to reorganize the city brand logo design, extract Gyeongju characteristics, based on residents’ lifestyle, city culture, historical cultural. The suggests a consistent city identity for domestic cities that yearn for global tourism cities，city identity should be systematically explored in city brand strategy.